63x + x2 -6x +7 x -3​

Answers

Answer 1
Answer: 66x-3
You have to reorder the terms and then collect like terms and you will get ur answer which is 66x-3
Answer 2
Answer: 63x-3 is the answer

Related Questions

The concept of volume is something you experience everyday in your life. Provide a specific example in which you could solve a real-world application using volume.
Can someone help or explain the problem to me
From 126 ounces to 48 ounces as a percent
2. The height of one solid limestone square pyramid is 24 m. A similar solid limestone square pyramid has a height of 30 m. The volume of the larger pyramid is 16,000 m3. Determine each of the following, showing all your work and reasoning. The ratio of the area of the base of the smaller pyramid to the larger pyramid (c) Ratio of the volume of the smaller pyramid to the larger (d) The volume of the smaller pyramidPlease help...LOTS OF POINTS
What is the monthly paycheck of an office manager whose salary is $57,000 per year

A 2-column table with 5 rows titled Fruit Prices. Column 1 is labeled fruit with entries apples, cherries, grapes, pears, strawberries. Column 2 is labeled Cost (per pound) with entries 1 dollar and 59 cents, 5 dollars and 28 cents, 2 dollars and 78 cents, 1 dollar and 41 cents, 3 dollars and 12 cents. Randy has $15 to spend on fruit. Using only estimation, which quantities of fruit can Randy reasonably buy? Check all that apply. 7.2 pounds of apples 4.1 pounds of cherries 6.89 pounds of grapes 10.75 pounds of pears 4.22 pounds of strawberries

Answers

Answer:

The answer is actually 1, 4, and 5.

Step-by-step explanation:

Answer:

The answer is 1, 4, and 5.

If $396 is invested at an interest rate of 13% per year and is compounded continuously, how much will the investment be worth in 3 years?

Answers

if the interest is compound (yearly) then is calculated by 
A = P (1+r)^(t)

then after 3 years the investment will worth

396(1.13)^3 = $571.38

Answer:

\$584.88  

Step-by-step explanation:

we know that

The formula to calculate continuously compounded interest  is equal to

A=P(e)^(rt)  

where  

A is the Final Investment Value  

P is the Principal amount of money to be invested  

r is the rate of interest  in decimal


t is Number of Time Periods  

e is the mathematical constant number

we have  

t=3\ years\n P=\$396\n r=0.13  

substitute in the formula above  

A=\$396(e)^(0.13*3)=\$584.88  


Reed uses 88 pieces of glass per square foot to make a stained glass window. how many pieces of glass will he need to make a window that is 864square inches?

Answers

He will need 528 pieces of glass.

Hope this helps!

Please mark as brainliest because it helps me out a lot :)

How do you solve this? 18 " n=21

Answers

18 ^(n) =21

log(18) ^(n)=log(21)

n*log(18)=log(21)

n= (log(21))/(log(18))

n=1.053

If f(x)=log2(x+4), what is f^-1(3)?

Answers

f\left( x \right) =\log _( 2 ){ \left( x+4 \right)  } \n \n \log _( 2 ){ \left( x+4 \right)  } =y\n \n { 2 }^( y )=x+4

\n \n x={ 2 }^( y )-4\n \n \therefore \quad { f }^( -1 )\left( x \right) ={ 2 }^( x )-4\n \n \therefore \quad { f }^( -1 )\left( 3 \right) ={ 2 }^( 3 )-4=4

The value of f^-1(3) is 4

What are inverse functions?

The inverse of a function f(x) is the opposite of the function

How to determine the inverse function?

The functionf(x)is given as:

f(x) = log_2(x + 4)

Express f(x) as y

y = log_2(x + 4)

Swap the positionsof x and y

x = log_2(y + 4)

Express as exponents

2^x = y + 4

Make y the subject

y = 2^x - 4

Express the equationsas an inverse function

f^(-1)(x) = 2^x - 4

Substitute 3 for x in the above equation

f^(-1)(3) = 2^3 - 4

Evaluate

f^(-1)(3) = 4

Hence, the value of f^-1(3) is 4

Read more about inverse functions at:

brainly.com/question/14391067

#SPJ5

What is the value of the expression (3a-b)/(6(b+a)) when a = 4 and b = -2?

Answers

Answer:-2

Step-by-step explanation:3(4) - (-2) ÷ 6(-2) + 4

= 12 + 4 ÷ -12 + 4

= 16 ÷ -8

= -2

Answer:

It will be 7/6

Step-by-step explanation:

Plug the values of a and b in the expression

You should take care in the fraction first

Then it will be ( 12 + 2 )/ 6 (-2+4)

= 14 / 12 = 7/6